High level of gentamicin resistance (HLGR) among enterococcus strains isolated from clinical specimens - Narges Dadfarma; Abbas Ali Imani Fooladi; Mahvash Oskoui; Hamideh Mahmoodzadeh Hosseini (Elsevier, 2013)
Summary: Background: Enterococci are pathogens that can cause nosocomial infections and acquire resistance properties via several molecular mechanisms. The aac (6')Ie-aph(2")Ia gene plays a significant role in the emergence of high-level gentamicin-resistant (HLGR) strains. The screening of resistant strains and the provision of appropriate antibiotic therapy can decide the outcome of serious nosocomial infections. Methods: In the present study, 142 enterococci were isolated from patients, and the species were identified using standard methods. An antimicrobial susceptibility test was performed using the disc diffusion method, and the minimum inhibition concentration (MIC) of gentamicin was determined according to the broth micro-dilution method. Additionally, PCR was utilized to detect the aac(6')Ie-aph(2")Ia gene, the presence of which was confirmed by digestion with Sca1 and sequencing. Results: Of the 142 isolates, 62 (43.7%) were found to exhibit the HLGR phenotype. All except one of the HLGR isolates contained the aac(6')Ie-aph(2")Ia gene. The prevalence of resistance to other antibiotics and multi-drug resistance (MDR) was higher among the HLGR isolates compared to the non-HLGR isolates. Conclusions: Our results indicate that high prevalence rates of MDR and HLGR enterococci are an important problem associated with medical treatment. Furthermore, the presence of the aac(6')Ie-aph(2")Ia gene was shown to correspond to the presence of the HLGR phenotype among enterococci. Keywords: High-level gentamicin resistance (HLGR), Enterococci, Minimum inhibitory concentration (MIC), Clinical specimens